История развития и перспективы совершенствования радиометеорного метода синхронизации шкал эталонов времени - Коваль, Ю. А.; Обельченко, В. В.; Нестеренко, Г. В.; Антипов, И. Е. (My University, 2005)
In work the following questions are considered: a history and a modern condition of a radiometeonc synchronization method (RMS) of time and frequency standards; results of radiometeonc comparisons of time scales of standards on a line Kharkov - Moscow by regular measurements: an estimation of workability RMS for synchronization of communication networks in Ukraine; application of the equipment the METKA- 6M for synchronization of time standard scales of the consumers which are taking place in a zone of direct visibility; perspective directions of increase of accuracy of a radiometeonc synchronization method.
Keywords: Кащеев Б. Л.; сети коммуникации; радиометрический метод; стандарт частоты; метод синхронизации